Evaluating the Impact of AI Tools on Grammar Mastery: A Comparative Study of Learning Outcomes - Lalira, James Edward; Yopie A. T. Pangemanan; Jane E. Scipio; Sjerly Lumi; Theo Ch. Merentek; Vivi Nansy Tumuju (VELES Voices of English Language Education Society, 2024)
Artificial Intelligence (AI) tools are increasingly integrated into education, offering innovative solutions to enhance learning, particularly in language acquisition. In grammar instruction, tools like Grammarly and ChatGPT provide real-time feedback, error correction, and personalized learning experiences. This study investigates the impact of these AI-assisted learning tools on grammar proficiency among students from diverse academic programs in two higher education institutions in Indonesia. A quasi-experimental design was employed, comparing pre-test and post-test grammar scores to evaluate the effectiveness of these tools. A total of 150 students participated, representing programs such as Nursing, Pharmacy, Health Administration, Economics Education, and English Education. The findings revealed significant improvements in grammar scores, particularly among students in non-language-focused programs, with an average increase of 15%. Students in the English Education program showed smaller gains (5%), attributed to their higher baseline proficiency. While the results demonstrate the potential of AI tools in enhancing grammar accuracy, concerns were raised about over-reliance on technology and the need for transparent integration in educational contexts. The absence of qualitative insights and long-term retention data are acknowledged as limitations. This study highlights the importance of using AI as a supplementary resource to support meaningful grammar learning, especially for students with limited exposure to formal language instruction.